2009
DOI: 10.1583/08-2646.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity on In-Hospital and Midterm Outcomes After Endovascular Repair of Abdominal Aortic Aneurysm

Abstract: Obesity is associated with extended operation times during EVAR, but increasing BMI appears to have little influence on outcomes after EVAR. A preferential approach to offering EVAR for obese patients may be reasonable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Smaller studies have shown inferior perioperative results among obese patients undergoing EVAR with no difference in long-term outcomes or mortality. 17,18 In a case-control study of 159 patients undergoing EVAR, Saratzis et al 16 found increased rates of perioperative complications among the obese cohort (e.g., wound infections and iliac-limb thromboses) but no difference in mortality or aneurysm-related morbidity. In another retrospective study of 80 patients undergoing EVAR, Jonker et al 18 did not identify any differences in perioperative or long-term complications between obese and nonobese patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller studies have shown inferior perioperative results among obese patients undergoing EVAR with no difference in long-term outcomes or mortality. 17,18 In a case-control study of 159 patients undergoing EVAR, Saratzis et al 16 found increased rates of perioperative complications among the obese cohort (e.g., wound infections and iliac-limb thromboses) but no difference in mortality or aneurysm-related morbidity. In another retrospective study of 80 patients undergoing EVAR, Jonker et al 18 did not identify any differences in perioperative or long-term complications between obese and nonobese patients.…”
Section: Discussionmentioning
confidence: 99%
“…14 Smaller studies have shown inferior perioperative results with no difference in long-term outcomes or mortality among obese patients undergoing EVAR. 17,18 The goal of this study was to identify the effect of BMI on perioperative and postoperative outcomes for patients undergoing elective EVAR.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these reports indicate that obesity may be associated with increased mortality following OAR. 1,11 In contrast, some other studies indicate no significant differences in perioperative mortality following OAR or EVAR. 2,3,12 In addition, while many of these early studies indicate that wound infections are increased in obese patients, 2,13 other investigators provide evidence against this relationship.…”
Section: Introductionmentioning
confidence: 98%
“…[4][5][6][7][8][9][10] In addition obesity has been proven to be an independent risk factor for adverse outcomes following general and cardiac surgical procedures. [11][12][13][14] The increase in the number of obese patients in all fields of surgery will produce numerous technical, logistical, and clinical challenges with respect to patient management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation